Assessment of the application for renewal of authorisation of Actisaf® Sc47 (Saccharomyces cerevisiae CNCM I‐4407) for lambs for fattening, minor dairy ruminants, horses and pigs for fattening. (11th July 2018) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria De Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the renewal of the authorisation of Actisaf Sc47 as a zootechnical additive for lambs for fattening, minor dairy ruminants, horses and pigs for fattening. In 2006, 2007 and 2008, the FEEDAP Panel adopted opinions on the safety and efficacy of Actisaf Sc47 when used in lambs for fattening, minor dairy ruminants, horses and pigs for fattening. Actisaf Sc47 is the trade name for a feed additive based on viable cells of Saccharomyces cerevisiae CNCM I‐4407 with no carrier. It is currently authorised for use in sows, piglets, pigs for fattening, cattle for fattening, calves for rearing, dairy cows, dairy buffaloes, lambs for fattening, dairy sheep, dairy goats, horses, rabbits for fattening and non‐food producing rabbits. Actisaf Sc47 is marketed in three forms: standard, powder and HR. All of them are authorised with a declared minimal concentration of viable yeast cells in the additive of 5 × 10 9  CFU/g. The applicant has provided data demonstrating that the additive currently in the market complies with the conditions of authorisation. In previous opinions, Actisaf Sc47 was presumed safe for the target species, consumers of products from animals fed the additive and the environment. Additionally, it was not found to be a skin or eye irritant. No new evidence has been identified that would make the FEEDAP Panel reconsider the previous conclusions on the safety of Actisaf Sc47. Therefore, the Panel considers that the additive Actisaf SC47 remains safe under the approved conditions for lambs for fattening, minor dairy ruminants, horses and pigs for fattening, the consumer, user and the environment.